Lamotrigine versus lithium augmentation of antidepressant therapy in treatment-resistant depression : efficacy an tolerability - Ivković, Maja, liječnica (Array, 2009)
Mood stabilizer augmentation of standard antidepressant drugs has been shown to be effective in treatment-resistant depression. Despite the reported high overall efficacy, lithium has been relatively underused in recent years. 88 patients suffering from treatment-resistant Major depressive disorder, having acute recurrent depressive episodes according to DSMIV criteria, were enrolled in the study. This was an open-label trial with a flexible dosing regimen. Patients were evaluated weekly for an 8 week treatment period.The HAM-D total score was significantly reduced in both treatment groups at the study endpoint, without any difference between the groups. However, significant clinical improvement was reached within the second treatment week in the lamotrigine group compared to the lithium group (p=0.01 vs. lithium)